Coordinated nitroxyl anion is produced and released as nitrous oxide by the decomposition of iridium-coordinated nitrosothiols - Kazhdan, Daniel (2011)
The aqueous decomposition of the iridium coordinated nitrosothiols (RSNOs) trans-K[IrCl4(CH3CN)NOSPh] (1), and K 2[IrCl5(NOECyS)] (2, ECyS = cysteine ethyl ester), was studied by MS analysis of the gaseous products, ESI-MS, NMR, and UV-Vis spectroscopy. Bent NO (NO-, nitroxyl anion), sulfenic acids and nitrite were observed as coordinated products in solution, while nitrous oxide (N2O) and nitrogen were detected in the gas phase. The formation of coordinated NO- and N2O, a nitroxyl dimerization product, allows us to propose the formation of free nitroxyl (HNO) as an intermediate. Complex 1 decomposes 300 times slower than free PhSNO does. In both cases (1 and 2) kinetic results show a first order decomposition behavior and a very negative ΔS≠, which strongly indicates an associative rate-determining step. A proposed decomposition mechanism, supported by the experimental data and DFT calculations, involves, as the first step, nucleophilic attack of H 2O on to the sulfur atom of the coordinated RSNO, producing an NO- complex and free sulfenic acid, followed by two competing reactions: a ligand exchange reaction of this NO- with the sulfenic acid or, to a minor extent, coordination of N2O to produce an NO -/N2O complex which finally renders free N2 and coordinated NO2-. Some of the produced NO- is likely to be released from the metal center producing nitroxyl by protonation and finally N2O by dimerization and loss of H2O. In conclusion, the decomposition of these coordinated RSNOs occurs through a different mechanism than for the decomposition of free RSNOs. It involves the formation of sulfenic acids and coordinated NO-, which is released from the complexes and protonated at the reaction pH producing nitroxyl (HNO), and ultimately N2O.